The sustainable development goals, master plans and the school curriculum: an interdisciplinary scoping review - De Albuquerque, Claudison V.; Cordeiro, António M. R.; Alcoforado, Joaquim L. M.; Carvalho, João A. R. (Frontiers in Education, 2024)
The Sustainable Development Goals of the United Nations, through the 2030 Agenda, seeks to address the various problems affecting the global population. For this, 17 goals and 162 subgoals were established, agreed by the member countries in 2015 at the COP 21 event in Paris. Therefore, the objective of this Scoping Review was to collect data produced in the world literature, which addressed themes linked to sustainability, education, curriculum, water and basic sanitation, in an integrated way, which dealt more specifically with goals 4 (Quality Education) and 6 (Water and Basic Sanitation) of the UN Sustainable Development Goals. It also aimed to find teaching networks in the most diverse countries, which used the curriculum, to bring the themes proposed by the UN into the classroom. To search for articles published in Portuguese, Spanish, and English, the period from June 2017 to June 2022 was taken into account. In addition, official guiding documents were also investigated. A total of 2,803 potential items were obtained. From this total, around 2,720 were eliminated for not meeting the guiding strings in this research, leaving 83 articles/documents. After further reading, 44 articles/documents met the inclusion and exclusion criteria. Data was found on all continents and in the most diverse countries, with different priorities. The countries that are part of the OECD have worked on these issues intending to improve their indicators. The so-called emerging countries (Brazil, Russia, China, India, South Africa, and Turkey, among others), on the other hand, treat the same data to improve educational metrics and universalize the quality of water supply and sanitation. Finally, in the countries that fall into the peripheral group, the findings were based on a rights guarantee approach, i.e., still from the perspective of implementing and consolidating public policies, such as some Latin American countries, South/Southeast Asia, and the vast majority of sub-Saharan African countries.